Kejadian Mikropenis pada anak obes - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Background: Obese children are more likely to have less testosterone, which may lead to disorder of penile development. Objective: To assess the association between obesity in children and the occurrence of micropenis. Method: A cross sectional study was carried out in 36 obese and 28 non- obese pubertal male children (10-13 years old) and 49 obese and 36 non-obese prepubertal male children (4-7 years old). Obesity was defined as body mass index (BMI) equivalent to or above the 95th percentile of the COC 2000 growth reference standard. Length of the penis was measured perpendicular to the surface of the as symphysis pubis to the tip of the glans penis. Skinfold thickness was measured on the area of mons pubis using a caliper. Volume of the testis was measured using an orchidometer. Results: The mean (SO) of penis length in 36 pubertal obese and 28 non-obese children were 5.56 (1.14) cm and 6.05 (1.37) cm, respectively